Effects of cranberry beverages on oxidative stress and gut microbiota in subjects with Helicobacter pylori infection: a randomized, double-blind, placebo-controlled trial. Issue 15 (15th June 2021) - Gao, Tao; Hou, Meiling; Zhang, Bo; Pan, Xin; Liu, Chengxia; Sun, Chongxiu; Jia, Mengru; Lin, Song; Xiong, Ke; Ma, Aiguo
Abstract : The current randomized double-blind placebo-controlled trial showed that cranberry beverages significantly improved the antioxidant status in Helicobacter pylori positive subjects, which may be related to the reshaping of the gut microbiota. Abstract : Helicobacter pylori -induced oxidative stress plays an important role in gastric diseases. H. pylori disturbs gut microbiota. The objective is to investigate the effects of cranberry beverages on oxidative stress biomarkers and gut microbiota in H. pylori positive subjects. 171 H. pylori positive participants were randomly assigned to one of the three groups: high-dose (HCb; 480 mL cranberry beverage), low-dose (LCb; 240 mL cranberry beverage plus 240 mL placebo) and placebo (480 mL). Subjects consumed the beverages daily for 4 weeks. Fasting blood samples were analyzed for oxidative stress biomarkers. The intestinal microbiome was analyzed by 16S rRNA sequencing. Compared with the placebo, HCb resulted in a significantly higher increase of total antioxidant capacity (mean ± SD: 1.39 ± 1.69 IU mL −1 vs. 0.34 ± 1.73 IU mL −1 ; p < 0.001) and a higher decrease of the lipid peroxidation product malondialdehyde (−7.29 ± 10.83 nmol mg −1 vs. −0.84 ± 15.66 nmol mg −1 ; p = 0.025). A significant dose-dependent effect on the elevation of superoxide dismutase was observed ( p < 0.001). Microbiome data showed that consuming HCb and LCb led to a significant reduction of Pseudomonas ( p < 0.05). In conclusion, the current research showed that consuming cranberry beverages significantly improved the antioxidant status in H. pylori positive subjects, which may be related to the reshaping of gut microbiota.